Inpatient autopsy rate and associated factors in a Chinese megacity: a population-based retrospective cohort study - Yu Wang; Jiming Zhu; Zihan Wang; Dachun Zhao; Hange Li; Yanrong He; Xidong Guo; Hanbo Zhang; Huatang Zeng (BMJ Open)
Objectives This study investigated the autopsy rate of hospital deaths in Shenzhen megacity and identified factors that may impact the decision to perform an autopsy in hospital deaths.Design This is a population-based retrospective cohort study.Setting Shenzhen is a megacity in China with a population of more than 17 million and a total of 151 hospitals. The official dataset of the inpatient medical record home page was used. Demographic, clinical and hospital information was extracted.Participants All the 35 272 inpatient deaths between 2016 and 2022 with known autopsy status were included to calculate the overall autopsy rate. Among them, a total of 34 577 cases with complete data, classified hospital and Chinese nationality, were included for further multivariable rare events logistic regression and Poisson pseudo maximum likelihood regression.Outcome measures Whether the inpatient death was autopsied or not.Results The autopsy procedure was performed in 0.9% (319/35 272) of hospital deaths. The autopsy decision was significantly and positively associated with being married (OR= 1.60, 95% CI: 1.16 to 2.21), self-paying (OR=1.56, 95% CI: 1.07 to 2.26), death due to external causes of injury and poisoning (OR=1.69, 95% CI: 1.02 to 2.81) and pregnancy (OR=13.58, 95% CI: 4.94 to 37.36), but negatively associated with age (OR=0.97, 95% CI: 0.96 to 0.98), emergency admission (OR=0.66, 95% CI: 0.49 to 0.88), referral (OR=0.47, 95% CI: 0.25 to 0.88), neoplasms (OR=0.35, 95% CI: 0.22 to 0.56), respiratory diseases (OR=0.49, 95% CI: 0.26 to 0.95) and for-profit hospitals (OR=0.45, 95% CI: 0.23 to 0.91). There were no statistically significant differences in autopsy rates between large teaching hospitals and other hospitals.Conclusions The autopsy rate of hospital deaths was extremely low, largely due to healthcare providers. Even large teaching hospitals do not request more autopsies compared with other hospitals, after controlling for the patient characteristics. More efforts are urged to encourage hospitals and healthcare providers to proactively request autopsies, helping to revive this important procedure.